Nanoparticle-based probes to enable noninvasive imaging of proteolytic activity for cancer diagnosis. (August 2016) - Anani, Tareq; Panizzi, Peter; David, Allan E.
Proteases play a key role in tumor biology, with high expression levels often correlating with poor prognosis for cancer patients – making them excellent disease markers for tumor diagnosis. Despite their significance, quantifying proteolytic activity in vivo remains a challenge. Nanoparticles, with their ability to serve as scaffolds having unique chemical, optical and magnetic properties, offer the promise of merging diagnostic medicine with material engineering. Such nanoparticles can interact preferentially with proteases enriched in tumors, providing the ability to assess disease state in a noninvasive and spatiotemporal manner. We review recent advances in the development of nanoparticles for imaging and quantification of proteolytic activity in tumor models, and prognosticate future advancements.